Anti-Müllerian hormone (AMH) downregulation in late antral stages is impaired in PCOS patients. A study in normo-ovulatory and PCOS patients undergoing in vitro maturation (IVM) treatments. (July 2013) - Kedem, Alon; Hourvitz, Ariel; Yung, Yuval; Shalev, Libby; Yerushalmi, Gil M.; Kanety, Hannah; Hanochi, Mirit; Maman, Ettie
Abstract Purpose: To prospectively study the AMH expression and secretion pattern in mural granulosa cells (GCs) and follicular fluid (FF) from small follicles and medium follicles that were collected from normo-ovulatory (NO) and polycystic ovary syndrome (PCOS) patients undergoing in vitro maturation (IVM) treatments. Methods: FF AMH levels and mRNA expression of mural GCs were measured in small (≤10 mm) and medium size follicles (11–15 mm) obtained from IVM treatments and large size follicles (≥16 mm) obtained from in vitro fertilization treatments. Results: First, we show that AMH expression and protein level in the FF of NO patients were significantly higher in the small size follicles than in the medium and large size follicles (p < 0.003). We could not demonstrate these differences in PCOS patients. Second, we found significantly higher levels of AMH protein and mRNA in the large and medium (but not small) size follicles of PCOS patients compared to follicles from NO patients (p < 0.02). Finally, we observed a positive correlation between FF AMH of small and medium size follicles from NO patients and serum AMH (p < 0.03 and p < 0.0002, respectively). Conclusions: Our data demonstrate a pathological dysregulation of AMH expression and secretion in follicles from PCOS patients and emphasize the association between the physiological downregulation of AMH and follicular antral health.